2002
DOI: 10.1055/s-2002-34493
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Adenylosuccinate Lyase Deficiency: Clinical, Biochemical and Molecular Findings in Four Patients

Abstract: Adenylosuccinate lyase deficiency is an autosomal recessive defect of purine metabolism. Succinyladenosine (S-Ado) and succinylaminoimidazole carboxamide riboside (SAICAr) are the disease marker metabolites in physiological fluids. The Bratton-Marshall test for detection of SAICAr in urine has been added to the selective screening for inborn errors of metabolism that is carried out in our lab. During the last three years, around 2,000 patients have been screened by this method, resulting in the detection of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…The mutations that we investigated in the present study are found paired in patients as follows: R396H/L311V (37) and R396C/R194C (9). These two patients have been described as having severe mental retardation while the two reported patients with the K246E mutation exhibit moderate to severe mental retardation (38).…”
Section: Discussionmentioning
confidence: 97%
“…The mutations that we investigated in the present study are found paired in patients as follows: R396H/L311V (37) and R396C/R194C (9). These two patients have been described as having severe mental retardation while the two reported patients with the K246E mutation exhibit moderate to severe mental retardation (38).…”
Section: Discussionmentioning
confidence: 97%
“…Seizures usually start either early in the neonatal period or after the first year of life (Van den Berghe et al 1998;Castro et al 2002) and are intractable.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with type II (moderate or mild form), who develop symptoms within the first years of life, usually suffer from slight to moderate psychomotor retardation and transient contact disturbances [7,9,10,13,21]. Seizures, if present, appear later, often between the second and fourth year of life [2,10]. Recently, a larger number of patients with a neonatal form have been reported [10,11,14,17,22].…”
Section: Introductionmentioning
confidence: 99%